2020
DOI: 10.48550/arxiv.2008.04634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FRBs: the Dispersion Measure of Host Galaxies

M. Jaroszynski

Abstract: Using the results of the IllustrisTNG simulation we estimate the dispersion measure which may be attributed to halos of so called host galaxies of fast radio bursts sources (FRBs). Our results show that in contradiction to assumptions used to show the applicability of FRBs to cosmological tests, both the dispersion measure and its standard deviation calculated for host galaxies with given stellar mass in general increase with the redshift. The effect is not strong and cosmological tests using FRBs will be poss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Using cosmological simulations to model baryonic distribution, [36] obtained results well fit by σ IGM ≈ 210 √ z. Further recent simulations bear this out [24,45,[49][50][51][52], and as in [25,27] we adopt…”
Section: B Dispersion Measure Componentsmentioning
confidence: 88%
“…Using cosmological simulations to model baryonic distribution, [36] obtained results well fit by σ IGM ≈ 210 √ z. Further recent simulations bear this out [24,45,[49][50][51][52], and as in [25,27] we adopt…”
Section: B Dispersion Measure Componentsmentioning
confidence: 88%
“…The factor 1 + z accounts for cosmological time dilation for a source at redshift z. The uncertainty σ IGM describes the deviation of an individual event from the mean DM IGM , due to the inhomogeneity of the baryon matter in the IGM, and we adopt the form [126]…”
Section: Jcap06(2023)052mentioning
confidence: 99%
“…A more reasonable way to deal with DM host is to model it as a probability distribution and marginalize over the free parameters. It is shown that DM host can be fitted with log-normal distribution from theory and cosmological simulations [55,92,93]. Therefore, instead of assuming a constant DM host , we model it as a log-normal distribution centered at DM host and refit the data.…”
Section: -6mentioning
confidence: 99%